Effect of methyl parathion on blood parameters and its recovery in a catfish, Mystus keletius - Sampath, K; James, R; Velammal, S (Indian Journal of Fisheries, 2011)
Effects of sublethal concentrations (0, 50, 100 or 200 ppb) of methyl parathion (MP) on haematological parameters and their complete recovery were studied in a catfish, Mystus keletius. Exposure to sublethal levels of MP elicited time and dose dependent significant decrease in red blood corpuscle (RBC) count, haemoglobin (Hb) content, haematocrit (Ht) value leading to anaemia. Anaemic condition may be due to inhibition of erythropoiesis, destruction of matured erythrocytes and haemodilution. Total Leucocyte Count (TLC) and Erythrocyte Sedimentation Rate (ESR), on the other hand, exhibited time and dose dependent increase. The increase in TLC was due to the increase in the population of lymphocytes, neutrophils and basophils, however, thrombocyte population showed a gradual decline. During recovery treatments, the trends were reversed. Extrapolation of recovery showed that, on an average, the blood parameters (RBC, Hb or TLC) of fish exposed to 50, 100 or 200 ppb took 44, 40 or 39 days respectively for complete recovery.